2023
DOI: 10.1017/jfm.2023.329
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds number dependence of the turbulent/non-turbulent interface in temporally developing turbulent boundary layers

Abstract: Direct numerical simulations (DNS) of temporally developing turbulent boundary layers are performed with a wide range of Reynolds numbers based on the momentum thickness $Re_{\theta } = 2000$ – $13\,000$ for investigating the Reynolds number dependence of the turbulent/non-turbulent interface (TNTI) layer. The grid spacing in the DNS is determined carefully such that small-scale turbulent motions near the TNTI are well resolved. The outer edge of the TNTI l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…The comparison of interface thickness with previous results by Zhang et al. (2018 b , 2023) is shown in figure 15. It has been found that as the increases, the mean thickness of the TNTI remains almost unchanged within approximately (Zhang et al.…”
Section: Interface Geometric Featuresmentioning
confidence: 55%
See 2 more Smart Citations
“…The comparison of interface thickness with previous results by Zhang et al. (2018 b , 2023) is shown in figure 15. It has been found that as the increases, the mean thickness of the TNTI remains almost unchanged within approximately (Zhang et al.…”
Section: Interface Geometric Featuresmentioning
confidence: 55%
“…2022; Xu, Wang & Chen 2023; Zhang et al. 2023). It can be seen that in figure 6( a ) the present work is fitted well with previous results, while in figure 6( b ) there are some differences above .…”
Section: Basic Characteristics Of the Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…This interface is dominated by small-scale-like instabilities, as observed from Figs. 3a-d, and can result in an intermittent flow behavior (Zhang et al, 2023). Due to the distinct separated shear layer observed for the smooth bed flow, this thin region persists until x/t = 1.5, but not visible for the rough bed case.…”
Section: 𝑑𝑦mentioning
confidence: 98%
“…The shear layer interface at the leading-edge is dominated by small rollups akin to KH-type instabilities that enhance small-scale entrainment into the separated shear layer (Fang et al, 2022;Stella et al, 2017;Vadlamani et al, 2018). The small-scale instabilities grow along the interface and are eventually absorbed into the separation bubble (Wei et al, 2024;Zhang et al, 2023). It is obvious that the bottom roughness heavily impacted the separated shear layer beneath the cover.…”
Section: 𝑑𝑦mentioning
confidence: 99%